Pengaruh Konsentrasi dan Frekuensi Pemberian Pupuk Organik Cair (POC) Terhadap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.). - Moh. Khanif Nasuha; Sarjana Parman; Rini Budi Hastuti (Jurnal Akademika Biologi, 2015)
Shallots (Allium ascalonicum L) is a vegetable crop that has an important role in the economy  of  Indonesian  society.  This  can  be  seen  from  the  BPS  (Central  Bureau  of Statistics) on onion  consumption in the country in 2014 amounted to 935,000 tons. The high consumption of red onion  cultivation resulted not memperhatiakan environmental factors are often farmers excessive use of inorganic fertilizers, resulting in soil becomes solid. Giving treatment Liquid Organic Fertilizer (POC) is expected to increase growth and yield of onion because the content of the complete haranya both micro and macro, and is also able to improve soil quality. The purpose of this research know the effect of the concentration, frequency and interaction of liquid organic fertilizer on the growth and production  of  onion  (Allium  ascalonicum  L).  The  design  used  in  this  research  was Randomized Complete Block  Design (RCBD) factorial design with two factors, namelythe concentration  of  fertilizers  and  the  frequency  of  fertilizer  application.  This  study menggunakan6  treatment with a combination of concentration and frequency are K0F1 (0% 5 days), K0F2 (0% 10 days), K1F1 (25% 5 days), K1F2 (25% of 10 days), K2F1 (50% 5 days), K2F2 (50% of 10 days). Observations made during the 50 days after planting. Growth  parameters measured were plant height and number of leaves, the production parameters measured were wet weight, dry weight, and the number of tubers. Data analysis using ANOVA test and further tests using  test Duncan Multiple Test (DMRT) at 95% confidence level. The conclusion of this research is the  concentration of liquid organic fertilizer (POC) significantly affect the growth parameters and onion production and the frequency and interaction no significant effect on growth parameters and onion production. Keywords: onion, organic fertilizer, concentration, frequency.